Quality of implementation of structural components of competitive programs of qualified athletes, as a factor determining the sporting result in acrobatic rock and roll - Луценко, Юлія (Slobozhanskyi Herald of Science and Sport, 2018)
Yuliya Lutsenko Purpose: to analyze modern competitive programs of "B" class athletes specializing in acrobatic rock and roll, and to determine the most informative indicators of the contents of these programs. Material & Methods: during the study, video footage of the speeches at the Ukrainian Championship in acrobatic rock and roll of sports pairs of class "B" and electronic protocols of these competitions were analyzed. To assess the relationship between the most informative indicators of the content of competitive programs, a correlation analysis. Results: it is determined that the most informative indicators of the content of the competition composition of qualified athletes of the "B" class, specializing in acrobatic rock and roll, are "elements of acrobatics and combinations", "main move", "dance figures", and in the block "choreography" "changes on the main move", "variation of the main move", "dance pair figures without the main move". Conclusions: a strong correlation was found between "acrobatics" and "acrobatic combinations" (0,95), between "changes in the main move" and "main move" (0,89), between "variations in the main move" and "main move" (0,91), between "variations of the main move" and "changes in the main move" (0,93), between "dancing pair figures without the main move" and "dance figures" (0,94).